Construction of polypropylene composite multifilaments filled with sodium perborate trihydrate-treated jute microparticles - Seki Yasemin; Akşit Aysun; Erdoğan Umit Halis (Science and Engineering of Composite Materials, 2017)
Polypropylene composite multifilaments filled with surface-treated jute microparticles were successfully spun by melt spinning. To enhance the particle distribution, jute particleos were treated with 5–20% (w/v) aqueous solutions of sodium perborate trihydrate (SP). X-ray photoelectron spectroscopy (XPS) was used to confirm the surface treatment. XPS analysis indicated that the treatments improved the hydrophobicity of the jute by means of increasing the carbon/oxygen ratio of the surface; thus, the maximum increment was achieved after 10% (w/v) SP treatment. After determining the optimum SP concentration, the spinning of polypropylene composite multifilaments containing 0.3–1.4 wt% jute particles was employed. Differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) revealed the nucleating agent effect of the particles during crystallization in the filaments. The addition of fillers did not result in significant changes in the functional groups of polypropylene. The main output of this research is that polypropylene multifilaments incorporating 1.4 wt% jute particles presented the highest moisture absorption and hydrophilic character as determined by TGA, moisture content, and vertical wicking tests. It was concluded that particle content >0.3 wt% showed a tendency to agglomerate in the filament. Consequently, this study provided a new polypropylene filament having moisture absorbability performance, which can create potential applications in the textile industry.